Radiation reaction and renormalization for a photon-like charged particle - Yaremko, Yu. (Вопросы атомной науки и техники, 2007)
A renormalization scheme which relies on energy-momentum and angular momentum balance equations is applied to the derivation of effective equation of motion for a massless point-like charge. Unlike the massive case, the rates of radiated energy-momentum and angular momentum tend to infinity whenever the massless source is accelerated. The external electromagnetic fields which do not change the velocity of the particle admit only its presence within the interaction area. The effective equation of motion is the equation on eigenvalues and eigenvectors of the electromagnetic tensor. The same solution arises in Rylov's model of magnetosphere of a rapidly rotating neutron star (pulsar). Пораховані енергія-імпульс та момент кількості руху електромагнітного поля безмасового точкового заряду. На відміну від точкового джерела з ненульовою масою спокою, інтеграли руху, що переносяться полем прискореного безмасового заряду, необмежено зростають. Тому фотоноподібний заряд може існувати лише в такому зовнішньому полі, яке не змінює його швидкості. Ефективним рівнянням руху є рівняння на власні вектори та власні значення тензора напруженості зовнішнього електромагнітного поля. Таке ж рівняння виникає в запропонованій Риловим моделі магнетосфери пульсара. Найдены енергия-импульс и момент количества движения электромагнитного поля безмассового точечного заряда. В отличии от точечного источника с ненулевой масссой покоя, излученные интегралы движения поля ускоренного безмассового заряда неограниченно возрастают. Вследствиe этого фотоноподобный заряд может существовать лишь в таком внешнем поле, которое не изменяет его скорости. Эффективным уравнением движения является уравнение на собственные векторы и собственные значения тензора напряжения внешнего электромагнитного поля. Такое же уравнение появляется в предложенной Рыловым модели магнитосферы пульсара.